A preliminary investigation on the antimicrobial activity of tsaang-gubat (Ehretia microphylla) leaf extract. - Villanueva, Lowella Aristorenas (2002.)
From standard solution of the aqueous extract of the. The effectiveness was tested on the growth of S. aureus, S. epidermidis, S. saprophyticus and C. albicans. The extract has weak inhibitory activity against S. aureus at 100 25 50 75 The study was conducted to find out if Ehretia microphylla have antimicrobial property. Four concentrations were prepared (100 and 75 concentration and against S. epidermis and S. saprophyticus at 100 concentrations. C. albicans did not exhibit response to the inhibitory effect on the leaf extract. (p)Negative control used was sterilized distilled water while positive controls used were Amoxicillin for the bacteria and Myscostatin for the yeast.
Special Problem (Undergraduate, Bachelor of Science in Biology) College of Arts and Sciences, University of the Philippines Visayas, Miagao, Iloilo
Keywords: Ehretia Microphylla; Tsaang-gubat.